ИСПОЛЬЗОВАНИЕ УФ СПЕКТРОФОТОМЕТРИИ ДЛЯ ВЫЯВЛЕНИЯ УСЛОВИЙ ЭКСТРАКЦИИ МЕТАПРОТА ИЗ ВОДНЫХ РАСТВОРОВ - T. H. Vergeychik; V. A. Linnikova; G. B. Guskova (Фармация и фармакология (Пятигорск), 2015)
We have studied conditions for metaprote extraction from water solutions with pH indices 1 – 12.45. We have also established that metaprote is maximally extracted with chloroform with pH index 6.86 – 9.19, with chloroform-acetone mixture 9:1 with pH index 4.01 – 12.45. We have determined the probability of UV spectrophotometry application for detection and identification of metaprote in extracts. The results received are recommended for use in development of method of metaprote isolation from biological liquids and its detection and identification with UV spectrophotometry for chemical and toxicological analysis